A Mini-Review on the Co-growth and Interactions Among Microorganisms (Fungi and Bacteria) From Rhizosphere of Metal-Hyperaccumulators - Cecchi, Grazia; Di Piazza, Simone; Rosatto, Stefano; Mariotti, Mauro Giorgio; Roccotiello, Enrica; Zotti, Mirca (Frontiers in Fungal Biology, 2021)
The co-growth and synergic interactions among fungi and bacteria from rhizosphere of plants able to hyperaccumulate heavy metals are largely unexplored. Fungi and bacteria contribute in an essential way to soil biogeochemical cycles mediating the nutrition, the growth development, and the health of associated plants, at the rhizosphere level. Microbial consortia improve the formation of soil aggregates and the soil fertility, producing organic acids and siderophores that increase solubility, mobilization and consequently the accumulation of nutrients and metals from the rhizosphere. These microorganism consortia can both mitigate the soil conditions promoting plant colonization and increase the performance of plant hyperaccumulators. Indeed, microfungi and bacteria from metalliferous soils or contaminated matrices are commonly metal-tolerant and can play a key role for plants in the phytoextraction or phytostabilization of metals. However, few works deepen the effects of the inoculation of microfungal and bacterial consortia at the rhizosphere level of metallophytes and their synergic activity. This minireview aims to collect and report the data regarding the role of microbial consortia and their potentialities known to date. Moreover, our new data are showed concerning an active fungal-bacteria consortium in the rhizosphere of the hyperaccumulator plant Alyssoides utriculata.